Kebijakan Standar Nasional Pendidikan pada Sekolah Dasar di Luwu Utara - Sakti, Supian; Ashariana, Ashariana; Bachtiar, Bachtiar; Nuddin, Nuddin (Journal of Government Insight, 2023)
This research analyzes the implementation of the National Education Standards Policy at North Luwu Elementary School using a naturalistic qualitative approach. The results show that the implementation of national standards is guided by government content standards. Even though the teaching staff and infrastructure are adequate, the main problem lies in inadequate funding. Educational assessment standards are uniform in all schools, including in student final exams.